Alkali-aggregate reaction in concrete a world review - Sims, Ian; Poole, Alan (CRC Press /Balkema, 2017)
This book is unique in providing authoritative up to date expert information on the causes and effects of alkali-aggregate reaction (AAR) in concrete structures. It has been compiled using expert contributions by acknowledged senior engineers and scientists from round the world.